2007
DOI: 10.1007/s00216-007-1121-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxymethylfurfural: an enemy or a friendly xenobiotic? A bioanalytical approach

Abstract: Hydroxymethylfurfural (HMF), a well-known heterocyclic Maillard reaction product, has often been studied for its potential toxic, mutagenic, and carcinogenic effects. Recent clinical studies, however, have strongly suggested that HMF might have exciting antitumor potential. We report on the development and validation of a bioanalytical assay for HMF that could be suitable as a basis for pharmacokinetic models in cancer patients. Two strategies were tested, i.e., direct and indirect methodologies. A direct isoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…The same was observed by Kowalski et al [2012], the increase caused by microwaves of the HMF is not gradual and its formation did not take place in the individual honeys in the same way, depending on fl oral origin. On the other hand, sample eight showed high concentration of HMF before treatment, associated to, probably, adultera- [Michail et al, 2007].…”
Section: Physicochemical and Thermal Propertiesmentioning
confidence: 93%
“…The same was observed by Kowalski et al [2012], the increase caused by microwaves of the HMF is not gradual and its formation did not take place in the individual honeys in the same way, depending on fl oral origin. On the other hand, sample eight showed high concentration of HMF before treatment, associated to, probably, adultera- [Michail et al, 2007].…”
Section: Physicochemical and Thermal Propertiesmentioning
confidence: 93%
“…In addition to concerns about negative impacts on health (Michail et al, 2007;N€ assberger, 1990), HMF is commonly used as a marker compound in foods and model systems (Garcia-Villanova, Guerra-Hernandez, Martinez-Gomez, & Montilla, 1993). This is because HMF is not only an intermediate product of Maillard reaction (Morales, Romero, & Jim enez-P erez, 1997) but also a degradation product of sugars at high temperatures (Kroh, 1994).…”
Section: Hmf Formation After Glycation At Various Conditionsmentioning
confidence: 97%
“…Among the low-molecular-mass products, large quantities of 5-hydroxymethyl-2-furaldehyde (HMF) are formed in certain foods (Rufián-Henares & de la Cueva, 2008;Wolfrom, Schuetz, & Cavalieri, 1948). Some recent studies show that HMF has often been found for its potential toxic, mutagenic and carcinogenic effects (Brusick, Jagannath, Galloway, & Nestmann, 1992;MacKenzie et al, 1992;Michail et al, 2007;Myers & Howell, 1992;Nassberger, 1990;Rasmussen, Hessov, & Bojsen-Moller, 1982;Ulbricht, Northup, & Thomas, 1984). For example, the studies reported that HMF has significant adverse effects on human blood cells (Michail et al, 2007;Nassberger, 1990).…”
Section: Introductionmentioning
confidence: 98%